RANCANG BANGUN ALAT PEMANAS AIR TENAGA SURYA DENGAN KONFIGURASI TUBE SERPENTINE BERKAPASITAS 100 LITER - Heriyanto Rusmaryadi; Rita Maria Veronika; Edy Purwanto (Jurnal Turbulen, 2018)
The purpose of this study is to test and determine the performance, and the factors that affect the performance of a solar water heater. The collector type is a flat plate and the configuration of collector pipe is serpentine. The results show that the important parameters are; the intensity of solar radiation, the sun's position for every hour, and the speed of the wind. The average efficiency of the solar water heater is 40.02%, while the average of the biggest  losses due to heat loss occur in the upper area of the collector box  is Ut = 2.09 W/m2.0C or 67.11% of total losses.  Keywords: Solar water heater, flat plate collector, serpentine, performance, losses